ANALYTICAL REVIEW OF SECURITY OF ENTERPRISES WITH FIXED ASSETS - TROSTIANSKA, Karina; FELONIUK, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the generalization of theoretical ideas about the provision of the enterprise with fixed assets and the improvement of the methodology of its analysis. The article discusses problematic aspects of the analysis of the enterprise’s provision of fixed assets. Methodical approaches to the analysis of the enterprise’s supply of fixed assets are defined, the sequence of the analysis is presented, and the system of indicators is defined. It is noted that in modern conditions there are no universal methods of assessing the level of provision of fixed assets of the enterprise, complex indicators of the level of provision in accordance with the goals of the organization have limited application, the optimal values of indicators of provision of fixed assets are not substantiated. It is proposed to use industry average values of indicators and indicators of competitors as guidelines for the level of the enterprise’s provision of fixed assets. The proposed methodological approach was tested on the example of competing companies in the food industry of the Dnipropetrovsk region.